Central blockade of nitric oxide synthesis reduces moxonidine-induced hypotension - Moreira, T. S.; Takakura, ACT; Menani, José Vanderlei [UNESP]; Sato, M. A.; Colombari, Eduardo [UNESP] (Nature Publishing Group, 2004)
1 Nitric oxide (NO) and alpha(2)-adrenoceptor and imidazoline agonists such as moxonidine may act centrally to inhibit sympathetic activity and decrease arterial pressure.2 In the present study, we investigated the effects of pretreatment with L-NAME ( NO synthesis inhibitor), injected into the 4th ventricle (4th V) or intravenously (i.v.), on the hypotension, bradycardia and vasodilatation induced by moxonidine injected into the 4th V in normotensive rats.3 Male Wistar rats with a stainless steel cannula implanted into the 4th V and anaesthetized with urethane were used. Blood flows were recorded by use of miniature pulsed Doppler flow probes implanted around the renal, superior mesenteric and low abdominal aorta.4 Moxonidine (20 nmol), injected into the 4th V, reduced the mean arterial pressure (-42+/-3 mmHg), heart rate (-22+/-7 bpm) and renal (-62+/-15%), mesenteric (-41+/-8%) and hindquarter (-50+/-8%) vascular resistances.5 Pretreatment with L-NAME (10 nmol into the 4th V) almost abolished central moxonidine-induced hypotension (-10+/-3 mmHg) and renal (-10+/-4%), mesenteric (-11+/-4%) and hindquarter (-13+/-6%) vascular resistance reduction, but did not affect the bradycardia (-18+/-8 bpm).6 the results indicate that central NO mechanisms are involved in the vasodilatation and hypotension, but not in the bradycardia, induced by central moxonidine in normotensive rats. British Journal of Pharmacology (2004).
Keywords: alpha(2)-adrenoceptors; imidazoline receptors; hypertension; nitric oxide; blood flow; vascular resistance; blood pressure